Evaluasi Penerapan Model Pembelajaran E-Learning pada Pelatihan Dasar Calon Pegawai Negeri Sipil: Evaluation of E-Learning Models Implementation in Basic Training of Prospective Civil Servants - Rahman, Muhammad Abdi; Amarullah, Rustan; Hidayah, Kemal (Pusjar SKPP Lembaga Administrasi Negara, 2020)
Technological developments in the industrial 4.0 revolution era have driven changes in the ways of work and use of resources in the digital era. Likewise, training mechanism, from conventional learning patterns to the network learning (online). Training and development in the government environment has discussed aggressively the concept of e-learning to provide new learning alternatives for trainees. This research used a qualitative-descriptive tried to evaluate the effectiveness of e-learning model in the Basic Training of Prospective Civil Servants. The results showed that the implementation of e-learning was effective enough to be used to increase participants' understanding of the training subjects. The quality and sustainability of the use of e-learning need to be improved so that it can effectively complement classical learning (blended learning). Mapping of efforts to optimize e-learning has also been identified starting from revamping the e-learning system/ application, learning facilitators, implementation time, and the need to adapt conventional learning elements. Keywords: E-learning, Training, Basic Training, Prospective Civil Servants (CPNS) Abstrak Kemajuan teknologi di era revolusi industri 4.0 telah mendorong terjadinya perubahan-perubahan cara kerja dan penggunaan sumber daya ke arah digital. Begitu juga mekanisme pelatihan, dari pola pembelajaran konvensional secara klasikal ke pembelajaran dalam jaringan (daring). Pelatihan dan pengembangan di lingkungan pemerintahan sudah mulai gencar mengadopsi konsep pembelajaran e-learning guna memberikan alternatif pembelajaran baru bagi peserta pelatihan. Penelitian ini secara kualitatif-deskriptif mencoba mengevaluasi efektivitas penerapan model pembelajaran secara e-learning pada lingkup Pelatihan Dasar Calon Pegawai Negeri Sipil. Hasil studi ini mengindikasikan bahwa implementasi e-learning cukup efektif digunakan untuk meningkatkan pemahaman peserta terhadap mata pelatihan. Kualitas dan keberlangsungan penggunaan e-learning perlu ditingkatkan sehingga dapat secara efektif melengkapi pembelajaran klasikal (blended learning). Pemetaan terhadap upaya mengoptimalkan e-learning juga telah diidentifikasi mulai dari pembenahan sistem/aplikasi e-learning, fasilitator pembelajaran, waktu pelaksanaan, dan perlunya adaptasi unsur-unsur pembelajaran konvensional. Kata kunci: E-learning, Pelatihan, Pelatihan Dasar, CPNS